2021
DOI: 10.26650/connectist2021-884955
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Pandemic News on Stock Market Returns During the Covid-19 Crash: Evidence from International Markets

Abstract: This study investigates the effect of pandemic-related news on stock market returns in international markets using the quantile regression method. The media hype index, fake news index, country sentiment index, infodemic index, and media coverage index provided by the RavenPack data platform are used for the analysis. In this research, 2,996 observations from 80 countries, consisting of daily data from January 22, 2020, to April 17, 2020, were used. The results show that the impact of Covid-19-related news on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 48 publications
3
2
0
Order By: Relevance
“…The greater the index value of the media frenzy regarding the COVID-19 issue, the more the Sharia stock index is corrected (down). This study supports previous studies from Tan (2021a;2021b) and Zargar and Kumar (2021), who found that the Media Hype Index on COVID-19 significantly negatively affected returns and stock prices both individually and collectively in the stock market. Conversely, this study presents contrasting findings to those of Rakshit and Neog (2021), who concluded that media frenzy about an incident positively affects stock market performance.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The greater the index value of the media frenzy regarding the COVID-19 issue, the more the Sharia stock index is corrected (down). This study supports previous studies from Tan (2021a;2021b) and Zargar and Kumar (2021), who found that the Media Hype Index on COVID-19 significantly negatively affected returns and stock prices both individually and collectively in the stock market. Conversely, this study presents contrasting findings to those of Rakshit and Neog (2021), who concluded that media frenzy about an incident positively affects stock market performance.…”
Section: Discussionsupporting
confidence: 91%
“…However, the fake news index and the contagion index were not found to affect the price movements of Islamic shares. This study also supports previous research stating that the critical elements of media effects that have a significant effect on Islamic capital markets in the three ASEAN countries are the panic index, media hype index, and sentiment index variables (Cepoi, 2020;Shi & Ho, 2021;TAN, 2021a). Although the fake news index has no significant effect on the Sharia stock index's movement, Indonesia has the highest fake news index, sentiment index, and panic index compared to the other two ASEAN countries in this study.…”
Section: Discussionsupporting
confidence: 90%
“…Due to high abnormal change, it triggered high volatility in the stock market. Our findings support prior research that utilized sentiment index as their explanatory variable (Baig et al, 2021;Tan, 2021).…”
Section: Discussionsupporting
confidence: 91%
“…Thereafter, the values moved towards positive numbers eventually (Buigut & Kapar, 2021). The positive sentiment positively affected stock prices (Tan, 2021). Therefore, we propose the hypothesis as follows:…”
Section: Sentiment Index (Si)mentioning
confidence: 89%
“…Olakojo et al [48] examined that the lower-income country had a lower impact than the higher-income country. Apart from the COVID-19 impact, false news and information can also increase the impact on the stock market [49]. Additionally, the commodity market was severely affected.…”
Section: Stock and Commodity Markets Consequencesmentioning
confidence: 99%